Facial morphology and obstructive sleep apnea - Anderson Capistrano; Aldir Cordeiro; Leopoldino Capelozza Filho; Veridiana Correia Almeida; Priscila Izabela de Castro e Silva; Sandra Martinez; Renata Rodrigues de Almeida-Pedrin (Dental Press Editora, 2015)
Objective: This study aimed at assessing the relationship between facial morphological patterns (I, II, III, Long Face and Short Face) as well as facial types (brachyfacial, mesofacial and dolichofacial) and obstructive sleep apnea (OSA) in patients attending a center specialized in sleep disorders. Methods: Frontal, lateral and smile photographs of 252 patients (157 men and 95 women), randomly selected from a polysomnography clinic, with mean age of 40.62 years, were evaluated. In order to obtain diagnosis of facial morphology, the sample was sent to three professors of Orthodontics trained to classify patients' face according to five patterns, as follows: 1) Pattern I; 2) Pattern II; 3) Pattern III; 4) Long facial pattern; 5) Short facial pattern. Intraexaminer agreement was assessed by means of Kappa index. The professors ranked patients' facial type based on a facial index that considers the proportion between facial width and height. Results: The multiple linear regression model evinced that, when compared to Pattern I, Pattern II had the apnea and hypopnea index (AHI) worsened in 6.98 episodes. However, when Pattern II was compared to Pattern III patients, the index for the latter was 11.45 episodes lower. As for the facial type, brachyfacial patients had a mean AHI of 22.34, while dolichofacial patients had a significantly statistical lower index of 10.52. Conclusion: Patients' facial morphology influences OSA. Pattern II and brachyfacial patients had greater AHI, while Pattern III patients showed a lower index.